Peningkatan Efisiensi Operasional WAZ-8 Laundry Melalui Pelatihan Pengelolaan Data dan Keuangan Menggunakan Microsoft Excel - Thanri, Yan Yang; Riza, Bob Subhan; Iriani, Juli; Subhan, Zhafira Nur; Zaidi, Luthfi (Publikasi Pengabdian Masyarakat, 2024)
Improving operational efficiency in laundry businesses greatly depends on effective data and financial management. WAZ-8 Laundry, a growing laundry business, faces challenges in managing transaction data and finances, which are still performed manually and ineffectively. Therefore, a training program on data and financial management using Microsoft Excel was organized to enhance operational efficiency and service quality provided to customers. This training aimed to equip WAZ-8 Laundry staff with the skills to manage transaction data, financial records, and operational reports effectively using Microsoft Excel. The training covered basic Excel techniques, table creation, data processing, the use of financial formulas, as well as financial report generation and data analysis for more accurate decision-making. By leveraging Excel features such as pivot tables, charts, and formulas, participants were expected to speed up the process of financial record-keeping and analysis, thereby identifying business trends and making better plans. The training employed a hands-on approach, with participants simulating data management and financial report generation in Excel. In addition, participants were also educated on the importance of accurate and structured data management to support better decision-making in laundry operations. Evaluation results indicated that most participants showed improved understanding of Excel usage, especially in financial report creation and transaction data analysis. Evaluation was conducted through pre-tests and post-tests, along with observation during the training. Post-test results showed an average score improvement of approximately 80%, reflecting better understanding of data and financial management. Participants also demonstrated improved abilities in operating Excel features such as pivot tables and financial formulas, which were previously less understood. Therefore, this training provides a significant impact on improving the operational performance of WAZ-8 Laundry, particularly in more efficient and effective data and financial management, ultimately supporting the business's growth.